How to strengthen self-discipline - Chuah, Michael (3 hours to master series, 2016)
When William's mum falls sick, he quickly realises his lack of self-discipline and overdependence on his mother. Can he learn to be less dependent and look after himself? Learn how to strengthen self-discipline and be more responsible with William and his classmates.